STRATEGI SUPPLY CHAIN MANAGEMENT PADA PT. MERCEDES-BENZ DISTRIBUTION INDONESIA - ranita; Derriawan; Miranda, Agustinus (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2022)
The purpose of this study was to see the effect of innovation, value chain and quality management system directly or indirectly on competitive advantage, and the influence of all these variables on enterprise resources planning of premium passangers car industry. The research sample was 30 respondents who were management level of Mercedes-Benz Distribution Indonesia. The sampling technique was puposive sampling. Data collection using questionnaires and FGD. The data were analyzed using Structural Equation Modeling (SEM) analysis processed with smartPLS software. The results of the study prove that the variables of innovation, value chain and quality management system have a significant effect on enterprise resources planning and enterprise resources planning has significant effect on competitive advantage. While quality management system variable has a significant effect on competitive advantage, however the innovation and value chain variables have no significant effect on competitive advantage.